Imagery Model of Pre-service Mathematics Teacher on Graphing Rational and Irrational Functions - Darmadi, Darmadi (Universitas Muhammadiyah Surakarta, 2018)
Students of mathematics teacher candidates are required to have good math and communication skills. Therefore, students of mathematics teacher candidates need to have good imagery modalities. With descriptive qualitative research method on the students of mathematics education program of FKIP Universitas PGRI Madiun, obtained the result that there are 10 models of students imaginary student of mathematics to graph of rational-irrational function. Mathematics learning or lectures need to be emphasized to enrich students imaginings on rational-irrational function graphs.Keywords: imagery, irrational-rational function Â Â Â